HPV-related HNC – new challenge and hope for head and neck cancer subjects (Journal of Medical Science, 2018)
In recent years there are observed substantial changes in epidemiology of head and neck cancer. An incidence of laryngeal cancer is declining as a consequence of decreased tobacco smoking. Contrary, oropharyngeal cancer associated with HPV infection transmitted on sexual way is becoming much more frequent. The latter one is characterized with a better prognosis that most likely does not require intensive therapy. De-escalation of therapy in case of HPV-associated tumor is a matter of current studies.